Hollow N‐doped carbon sphere synthesized by MOF as superior oxygen electrocatalyst for Li‐O2 batteries - He, Menglu; Jia, Jia; Sun, Qing; Zhang, Weixin (International journal of energy research, 2021)
SUMMARY Li‐O2 battery has attracted much attention due to its ultra‐high theoretical energy density in the field of electrochemical energy storage. The introduction of efficient electrocatalyst can effectively accelerate the reaction rate of ORR and OER, so as to improve the coulomb efficiency and poor cycle stability of Li‐O2 battery. In this work, a novel hollow N‐doped carbon sphere is prepared by using MOF and polystyrene as template, and act as highly efficient oxygen electrocatalyst for rechargeable Li‐O2 batteries. The hollow structure can provide enough oxygen diffusion channel, deposition and decomposition space for reduction products. N doping into the hollow carbon structure can increase the charge density of adjacent carbon atoms and enhance its catalytic activity of ORR/OER. As a result, the Li‐O2 battery using the hollow N‐doped carbon sphere as air cathode exhibited an high specific capacity of 18 762 mAh/g (at a current density of 500 mA/g) and remarkable cycling stability of 212 cycles (at a current density of 500 mA/g and limited capacity of 1000 mAh/g), outperforming the carbon material with common structure. This work highlights the importance of air cathode structure and efficient catalyst, provides a new idea for the design of air cathode of Li‐O2 battery, and expands the scope of future research. A novel hollow N‐doped carbon sphere is prepared by using MOF and polystyrene as template, and act as highly efficient oxygen electrocatalyst for rechargeable Li‐O2 batteries. The hollow structure can provide enough oxygen diffusion channel, deposition, and decomposition space for reduction products. N doping into the hollow carbon structure can increase the charge density of adjacent carbon atoms and enhance its catalytic activity of ORR/OER.